1991
DOI: 10.3109/03009749109165280
|View full text |Cite
|
Sign up to set email alerts
|

The Leukocyte Protein L1 in Plasma and Synovial Fluid from Patients with Rheumatoid Arthritis and Osteoarthritis

Abstract: L1 is a major granulocyte and monocyte protein, released during activation and turnover of such cells. Blood and synovial fluid (SF) from 41 patients with rheumatoid arthritis (RA) and 6 patients with osteoarthritis (OA), were analyzed for L1 and the acute phase proteins C-reactive protein, orosomucoid, haptoglobin, alpha 1-antitrypsin and albumin as well as for differential leukocyte count. L1 levels in plasma and SF showed highly significant differences (p less than 0.0001), between the RA and OA patients. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 28 publications
2
75
0
2
Order By: Relevance
“…The calprotectin-upregulated pathological states were also listed in more detail in a review by Johne et al 21) Berntzen et al reported that in healthy human serum/ plasma, the concentration of calprotectin was less than 1 mg/ml, while the plasma concentration of patients with rheumatoid arthritis (RA) was reportedly increased to approximately 10-fold higher concentrations as mean values. 30) In contrast, no substantial increase was observed in osteoarthritis. 30) An increase in blood calprotectin concentration was also reported in patients with Crohn's disease, 34) colorectal carcinoma, 35) cystic fibrosis, 36,37) multiple sclerosis, 38) human immunodeficiency virus (HIV) infection, 39) and patients who had undergone major surgery.…”
Section: Pathological States In Which Calpro-tectin Is Upregulatedmentioning
confidence: 67%
See 3 more Smart Citations
“…The calprotectin-upregulated pathological states were also listed in more detail in a review by Johne et al 21) Berntzen et al reported that in healthy human serum/ plasma, the concentration of calprotectin was less than 1 mg/ml, while the plasma concentration of patients with rheumatoid arthritis (RA) was reportedly increased to approximately 10-fold higher concentrations as mean values. 30) In contrast, no substantial increase was observed in osteoarthritis. 30) An increase in blood calprotectin concentration was also reported in patients with Crohn's disease, 34) colorectal carcinoma, 35) cystic fibrosis, 36,37) multiple sclerosis, 38) human immunodeficiency virus (HIV) infection, 39) and patients who had undergone major surgery.…”
Section: Pathological States In Which Calpro-tectin Is Upregulatedmentioning
confidence: 67%
“…30) In contrast, no substantial increase was observed in osteoarthritis. 30) An increase in blood calprotectin concentration was also reported in patients with Crohn's disease, 34) colorectal carcinoma, 35) cystic fibrosis, 36,37) multiple sclerosis, 38) human immunodeficiency virus (HIV) infection, 39) and patients who had undergone major surgery. 42) A more intense increase in calprotectin concentration has been observed in body fluid from local inflammatory sites than in blood.…”
Section: Pathological States In Which Calpro-tectin Is Upregulatedmentioning
confidence: 67%
See 2 more Smart Citations
“…Calprotectin induces the secretion of both IL-6 and TNF in a dose-dependent manner (10). Higher calprotectin levels have been found in synovial fluid and serum from RA and PsA patients compared with healthy controls and osteoarthritis patients (11). Calprotectin serum levels correlate with disease activity, predict relapse, and are independently associated with radiographic progression in RA (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%